Differential Gene Expression and Protein Phosphorylation as Factors Regulating the State of the Arabidopsis SNX1 Protein Complexes in Response to Environmental Stimuli - Brumbarova, Tzvetina; Ivanov, Rumen (Frontiers in Plant Science, 2016)
Endosomal recycling of plasma-membrane proteins contributes significantly to the regulation of cellular transport and signaling processes. Members of the Arabidopsis (Arabidopsis thaliana) SORTING NEXIN (SNX) protein family were shown to mediate the endosomal retrieval of transporter proteins in response to external challenges. Our aim is to understand the possible ways through which external stimuli influence the activity of SNX1 in the root. Several proteins are known to contribute to the function of SNX1 through direct protein-protein interaction. We, therefore, compiled a list of all Arabidopsis proteins known to physically interact with SNX1 and employed available gene expression and proteomic data for a comprehensive analysis of the transcriptional and post-transcriptional regulation of this interactome. The genes encoding SNX1-interaction partners showed distinct expression patterns with some, like FAB1A, being uniformly-expressed, while others, like MC9 and BLOS1, were expressed in specific root zones and cell types. Under stress conditions known to induce SNX1-dependent responses, two genes encoding SNX1-interacting proteins, MC9 and NXH6, showed major gene-expression variations. We could also observe zone-specific transcriptional changes of SNX1 under iron deficiency, which are consistent with the described role of the SNX1 protein. This suggests that the composition of potential SNX1-containing protein complexes in roots is cell-specific and may be readjusted in response to external stimuli. On the level of post-transcriptional modifications, we observed stress-dependent changes in the phosphorylation status of SNX1, FAB1A and CLASP. Interestingly, the phosphorylation events affecting SNX1 interactors occur in a pattern which is largely complementary to transcriptional regulation. Our analysis shows that transcriptional and post-transcriptional regulation play distinct roles in SNX1-mediated endosomal recycling under external stress.